2012
DOI: 10.2174/156720512804142840
|View full text |Cite
|
Sign up to set email alerts
|

Association between Hypocretin-1 and Amyloid-β42 Cerebrospinal Fluid Levels in Alzheimer’s Disease and Healthy Controls

Abstract: Alzheimer's disease is associated with sleep disorders. Recently, animal studies demonstrated a link between hypocretin, a sleep-regulation neurotransmitter, and AD pathology. In this study, we investigated the circadian rhythm of hypocretin-1 in Alzheimer's Disease (AD) patients and controls. Moreover, we assessed the relation between CSF hypocretin-1 and amyloid-β. A continuous CSF sampling study via indwelling intrathecal catheter was performed to collect hourly CSF samples of six patients with AD (59-85 yr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 47 publications
2
38
0
Order By: Relevance
“…There is growing evidence of the impairment of melanin-concentrating hormone and HCRT-1 systems in AD patients, that is, in post-mortem studies of the hypothalamus of AD patients and controls, a decrease in cell number and lower CSF HCRT-1 levels were found. Gender differences in CSF HCRT-1 have also been found, supporting the higher prevalence of sleep disturbances and AD in women [30,32,33] . In both human and mouse models, the level of Aβ increases during wakefulness and decreases during sleep following a circadian rhythm and is regulated by orexin [34][35][36] .…”
Section: Introductionmentioning
confidence: 72%
“…There is growing evidence of the impairment of melanin-concentrating hormone and HCRT-1 systems in AD patients, that is, in post-mortem studies of the hypothalamus of AD patients and controls, a decrease in cell number and lower CSF HCRT-1 levels were found. Gender differences in CSF HCRT-1 have also been found, supporting the higher prevalence of sleep disturbances and AD in women [30,32,33] . In both human and mouse models, the level of Aβ increases during wakefulness and decreases during sleep following a circadian rhythm and is regulated by orexin [34][35][36] .…”
Section: Introductionmentioning
confidence: 72%
“…A slight correlation between Aβ 42 and hypocretin-1 levels was recently reported in 6 patients with AD and 6 healthy controls, with no between-group difference in CSF hypocretin-1 levels and its circadian amplitude (Slats et al, 2012). In contrast, no association between Aβ 42 and hypocretin-1 was reported in either control subjects or patients with AD in a larger study, but with low hypocretin-1 levels in 9 female patients with LBD (Wennstrom et al, 2012).…”
Section: Discussionmentioning
confidence: 89%
“…However, several studies have reported a normal range of CSF hypocretin-1 concentration in AD patients (Mignot et al, 2002; Dauvilliers et al, 2003; Baumann et al, 2004; Friedman et al, 2007). One elegant study using an indwelling intrathecal catheter to collect hourly CSF samples in six patients with AD and six controls reported a correlation between hypocretin-1 and Aβ 42 , with no significant between-group differences in hypocretin-1 circadian rhythm amplitude (Slats et al, 2012). Moreover, lower CSF hypocretin-1 levels were found in dementia with Lewy bodies compared to AD and controls, with no associations between hypocretin-1 and Aβ 42 concentrations (Wennstrom et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the 3×Tg mouse model, a well-described early feature of human AD pathogenesis is degeneration of the locus coeruleus, the main source of norepinephrine to the cortex and a region critical for maintenance of normal wakefulness [35]. Deficits have also been identified in the wake-promoting molecule, orexin (also known as hypocretin), which is implicated in human narcolepsy: CSF orexin levels are significantly correlated with CSF Aβ42 levels in AD patients, suggesting decreased control of the sleep–wake cycle occurs with decreased Aβ42 levels (used as a surrogate marker for amyloid plaque deposition) [36]. Furthermore, CSF orexin levels have a significant correlation with tau and phosphorylated tau protein levels in the CSF of ten patients with AD compared with ten age-matched controls, indicating a relationship between sleep–wake molecules and tau pathology [37].…”
Section: Ad Pathology Disrupts Sleepmentioning
confidence: 99%